Evaluación del tiempo termal óptimo en mezclas forrajeras de rye grass, pasto azul, trébol blanco y kikuyo pastoreadas en la ganadería san Cristóbal del cantón Salcedo. - Bonilla Espinosa, Erik Marcelo (2020)
This research was carried out in the province of Cotopaxi, in the Salcedo, San Miguel Parish of “San Cristóbal” Farm. To evaluate the optimal thermal time in a forage mixture (Trifolium repens), (Lolium perenne), (Dactylis glomerata), and (Pennisetum clandestinum). For the feeding of grazed cattle, in order to determine the amount of temperature accumulated concerning the DNF of the regrowth passes to have consistent quality, determine the cost-benefit and evaluate the body condition of the animals thus establishing the feasibility of the investigation for which the bromatological and laboratory tests will analyze. The field study is carried out in the San Cristóbal farm, two thermometers of high and low temperatures will be placed in a particular pasture, the same ones that will give us the information of the temperatures 4:00 am and 4:00 pm during The time of the investigation was carried, on day 0 (05-Dec-2019) the first sample was taken and sent from the sample to the laboratory for bromatological analysis obtaining an FDN of 50.55, then the taking was made and sent the following sample of the forage mixture 30 days after regrowth (day 05-Jan-2020) for another bromatological analysis obtaining a 42.79 with a thermal sum of 132 ° C, the following sample was sent five days later (day 10-Jan-2020) having as result of the bromatological of FDN 44,10 and a thermal sum of 186 ° C and culminated with the taking and sending of the third sample to the following five days (15-Jan-2020) for the analysis with an FDN of 45.30 with a sum 217 ° C thermal. A total of 15 cows are used for the study; 5 in the first third of breastfeeding, 5 in the second third of breastfeeding, and 5 in the third third of breastfeeding. The procedure to take the weights of them, carry out a record of the daily milk production, and also the procedure to take and send blood samples for the BUN and in the urine for a body analysis ketones. We proceed to take the weights of the same, continue with the registration of milk production every day, and also a procedure will be performed to make the taking and blood samples will be sent to the BUN and urine for analysis of ketone bodies.